2004
DOI: 10.1103/physreve.69.016117
|View full text |Cite
|
Sign up to set email alerts
|

Direct test of the critical exponents at the sol-gel transition

Abstract: The steady state fluorescence technique was used to study the sol-gel transition for the solution-free radical cross-linking polymerization of acrylamide (AAm), with N,N'-methylenebis (acrylamide) as cross linker in the presence of ammonium persulfate as an initiator. Pyranine (8-hydroxypyrene-1, 3,6-trisulfonic acid, trisodium salt) is used as a fluoroprobe for monitoring the polymerization. Pyranine molecules start to bind to acrylamide polymer chains upon the initiation of the polymerization, thus the spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 36 publications
5
53
0
Order By: Relevance
“…Our recent observations around the critical point showed that the critical exponents did not obey the same universality class for neat AAm [13] and NIPA [14] hydrogels, while bulk gels [15][16][17][18] were modeled by percolation picture. In neat AAm hydrogels, it was shown that the critical exponents agree best with the percolation results for higher AAm concentrations above 1 M, but they crossover from percolation to classical (mean-field or Flory-Stockmayer) values when the AAm concentration goes from 2 M down to 1 M, and the present classical values below 1 M. Further down below 0.5 M, however, no gelation was observed.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Our recent observations around the critical point showed that the critical exponents did not obey the same universality class for neat AAm [13] and NIPA [14] hydrogels, while bulk gels [15][16][17][18] were modeled by percolation picture. In neat AAm hydrogels, it was shown that the critical exponents agree best with the percolation results for higher AAm concentrations above 1 M, but they crossover from percolation to classical (mean-field or Flory-Stockmayer) values when the AAm concentration goes from 2 M down to 1 M, and the present classical values below 1 M. Further down below 0.5 M, however, no gelation was observed.…”
Section: Resultsmentioning
confidence: 96%
“…In neat AAm hydrogels, it was shown that the critical exponents agree best with the percolation results for higher AAm concentrations above 1 M, but they crossover from percolation to classical (mean-field or Flory-Stockmayer) values when the AAm concentration goes from 2 M down to 1 M, and the present classical values below 1 M. Further down below 0.5 M, however, no gelation was observed. [13] The gel fraction (above the gel point) and average cluster size (below the gel point) exponents and the gel points (for 1 M PAAm hydrogel for various BIS contents) are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…As one can see from Figure 6 the intensity of the short-wavelength peak (380 nm-peak) increases during the course of polymerization, meanwhile as the polymerization progresses the maxima of the short wavelength-peak shifts to some higher wavelengths from 380 nm to 427nm (Kaya et al, 2004). Here at first the shift from 512 nm to 380 nm in the emission spectra due to a C-O ether bond formation between the hydroxyl oxygen of 3sPyOH and a terminal C-atom of the growing AAm chain.…”
Section: Sol-gel Exponentsmentioning
confidence: 99%
“…Above t gel , if the intensity from finite clusters distributed through the infinite network I ct is subtracted from the maximum fluorescence intensity, then, the corrected intensity I`-I ct measures solely the gel fraction G, the fraction of the monomers that belong to the macroscopic network. In summary, we have the following relations, (Kaya et al, 2004) '…”
Section: Sol-gel Exponentsmentioning
confidence: 99%
See 1 more Smart Citation